Prevalence and antimicrobial resistance patterns of Salmonella isolated from poultry farms in southeastern United States. (27th March 2018) - Velasquez, C G; Macklin, K S; Kumar, S; Bailey, M; Ebner, P E; Oliver, H F; Martin-Gonzalez, F S; Singh, M
ABSTRACT: Salmonella spp. are among the most common foodborne pathogens, and increase in the occurrence of antimicrobial drug-resistant Salmonella poses a severe risk to public health. The main objective of this study was to determine changes in Salmonella prevalence and their antimicrobial resistance on poultry farms following recommendations to changes in biosecurity practices. Four poultry farms were sampled by collecting cloacal swabs, drag swabs, and litter samples prior to recommended biosecurity changes (March–April) and post recommendations (October–November). Prevalence of Salmonella was 3 to 4% during pre-recommendations, while the prevalence was higher ( P > 0.05), ranging from 5 to 14% during post recommendations. Higher Salmonella prevalence was observed for pre- and post-recommendation phases by sample type in cloacal and drag samples −5% for farm 1, drag swab −6% on farm 2, cloacal swab −6% for farm 3, and drag swab −17% on farm 4. The PCR confirmed Salmonella were serotyped and tested for antimicrobial resistance. Six serotypes of Salmonella were identified with S . Enteritidis (52%) being the most prevalent, followed by S . Berta (38%), S . Mbandaka (7%), S . Typhimurium (2%), S . Kentucky (0.4%), and S . Tennessee (0.4%). A total of 7% isolates exhibited resistance to at least one of the 8 antimicrobials. Higher resistance was observed for tetracycline, streptomycin, and nalidixic acid. A single isolate of S. Mbandaka exhibited multidrug resistance to tetracycline, amoxicillin/clavulanic acid, and ampicillin. Based on these prevalence results, it can be inferred that, irrespective of implementation of improved biosecurity practices, seasonal variation can cause changes in the prevalence of Salmonella on the farms. Resistance to clinically important antimicrobials used to treat salmonellosis is a concern to public health.